Aneurysm of the poplıteal artery: Case report - (:unkn) unknown (My University, 2007)
Popliteal arter anevrizmalarının tedavi edilmediğinde birçok istenmeyen duruma neden olduğu bilinmektedir. Popliteal arter anevrizması nedeni ile alt ekstremite ağrısı ile başvuran 63 yaşındaki bir hastaya posterior yaklaşım ile safen ven interpozisyonu uygulanmıştır. Hastalığın tanısı ve tedavisi bu vaka sunumunda tartışılmaktadır.

Popliteal artery aneurysms lead to many uneventful conditions if left untreated. We report a case of a 63-year-old man who presented with a pain in the lower extremity as a result of a popliteal artery aneurysm. He underwent surgery through a posterior approach with saphenous vein graft interposition. The presentation, investigation and treatment of this condition is discussed.
Popliteal arter anevrizması: Vaka sunumu
Keywords: Genel ve Dahili Tıp